The Effectiveness of Team Games Tournament Method on Students’ Vocabulary Mastery in Junior High School - Julianto, Muhamad Safei (International Journal of English Education and Linguistics (IJoEEL), 2024)
The aim of this research method is to examine whether the implementation of the Team Games Tournament method influences students’ vocabulary mastery when describing extracurricular activities. Many students in areas that rarely use English as a second language find it difficult to master English. The problem that often occurs is the lack of motivation when students want to develop their English skills. The researcher collected data from 2 class VII students at SMP Islam Kunir. The subject of this research was the VII class; VII-A and VII-C had 27 students, and VII-B had 28 students. This research conducted quantitative method with quasi- experimental design . The data were collected using a vocabulary test. The mean of pre-test and post-test on control group are 51.43 and 71.25. While, The mean of pre-test and post-test on experimental gropu are 63.42 and 82.96.  The significance of the T-test result is (0,000), which means it is lower than (0,005). That means the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Based on the data results, the researcher found that the team game tournament method can improve students’ vocabulary mastery. This research only used one game, Describe and Mention. Many games can be used in the TGT method. The researcher hoped that future studies would use another game to understand the effect of the TGT method on vocabulary more comprehensively. Also, the researcher hoped that future studies would investigate other contexts, such as speaking, reading, writing, and listening.